X-RAY microtomographic studies of LC3 and related binders - Bernal, Isabel M.R.; Cuesta-García, Ana María; Santacruz-Cruz, María Isabel; Gómez-de-la-Torre, María de los Ángeles; García-Aranda, Miguel Ángel; Shirani, Shiva; Redondo-Soto, Cinthya; Olbinado, Margie P.; Salcedo, Inés R. (EPFL, 2022)
LC3 type cements do not need introduction in this conference, neither the importance of studying the microporosity features (amount, size(s), connectivities, etc.). However, analysing the porosity in an accurate, quantitative and robust way is far from easy/well-established. Here, we intend to contribute by analysing selected microporosity features and their evolution using synchrotron (and laboratory) X- ray microtomography (μCT) with the final goal of gaining a deeper insight into the microstructures of LC3 binders. Nowadays, synchrotron μCT allows obtaining tomograms in binders with voxel sizes of 0.3 μm and true spatial resolution close to 1.0 μm [1]. Additionally, for this work, the detector was placed at 5.5 mm from the samples and therefore, phase-propagation increased the visibility between components with similar attenuations to the X-rays. The Paganin phase retrieval algorithm [2] was employed which resulted in augmented contrast. Moreover, another advantage is that fast acquisition times are possible, i.e. a full high-resolution tomogram can be recorded in 5 minutes.
n.a.
Keywords: Cemento - Congresos; Cemento - Tomografía - Congresos; X-ray imaging; Cements; Low-CO2 footprint; Microtomography